2006
DOI: 10.1159/000092292
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Epidermolysis Bullosa Acquisita with Autoantibody to Anti-p200 Pemphigoid Antigen and Exfoliative Esophagitis

Abstract: Background: Some cases of a subepidermal blistering disease associated with autoantibodies to more than two antigens have been reported. Observation: A 52-year-old Japanese woman had pruritic blisters on almost the whole body as well as erosive lesions in the oral cavity and esophagus. A histological finding was subepidermal bullae. Direct immunofluorescence (IF) revealed a linear deposition of IgG, IgM and C3 at the epidermal basement membrane zone (BMZ). Indirect IF using human skin split by 1 M NaCl as a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…In these 2 patients, immunoblotting analyses demonstrated the presence of autoantibodies against both laminin yl and laminin-332, as in our case. Similarly, it has been reported that anti-p200 pemphigoid sera contained other target antigens of the dermal-epidermal junction, such as BP180 (3-7), BP230 (4,7,8), the a3 chain of laminin 332 (1) and the type VII collagen (9,10). A high degree of sequence homology is observed between laminin yl and laminin-332 y2 (34% identity and 27% similarity; Blastp Align, NCBI).…”
Section: Discussionmentioning
confidence: 73%
“…In these 2 patients, immunoblotting analyses demonstrated the presence of autoantibodies against both laminin yl and laminin-332, as in our case. Similarly, it has been reported that anti-p200 pemphigoid sera contained other target antigens of the dermal-epidermal junction, such as BP180 (3-7), BP230 (4,7,8), the a3 chain of laminin 332 (1) and the type VII collagen (9,10). A high degree of sequence homology is observed between laminin yl and laminin-332 y2 (34% identity and 27% similarity; Blastp Align, NCBI).…”
Section: Discussionmentioning
confidence: 73%
“…Reactivity against multiple antigens of the DEJ is not uncommon in autoimmune subepidermal bullous diseases and is likely to be due to intermolecular epitope spreading 24 . In fact, a substantial number of anti‐p200 pemphigoid sera has previously been described to contain antibodies against other target antigens of the DEJ, including BP180, 3,25–27 BP230, 1,25 the α3 chain of laminin 332, 28 and type VII collagen 29,30 . Most recently, we have described a patient with anti‐p200 pemphigoid who developed additional anti‐BP180 NC16A autoantibodies during the course of his disease 27 .…”
Section: Discussionmentioning
confidence: 97%
“…39,63,66,67 Of note, the presence of circulating autoAbs against BP180, laminin 332 and the p200/laminin c1 chain (detected by IB or ELISA), which may occur as a result of the epitope spreading phenomenon, does not rule out a diagnosis of EBA (supplementary cases 2 and 4 in Appendix S2). 37,[68][69][70][71][72][73][74][75] Novel technique: indirect immunofluorescence using noncollagenous 1 type VII collagen-transfected cells Patient serum autoAbs could label NC1 Col7-transfected cells on a special slide, a so-called BIOCHIP TM method (Fig. 5).…”
Section: Enzyme-linked Immunosorbent Assaymentioning
confidence: 99%